2009
DOI: 10.4081/jlimnol.2009.106
|View full text |Cite
|
Sign up to set email alerts
|

A numerical index for evaluating phytoplankton response to changes in nutrient levels in deep mediterranean reservoirs

Abstract: This paper proposes a new ecological index based on phytoplankton (MedPTI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 35 publications
4
66
0
Order By: Relevance
“…The reservoirs were classified as eutrophic (Cantonieria, Mulargia, Gusana, Monte Lerno, Benzone, Is Barrocus, Leni and Cucchinadorza), mesotrophic (Medio Fludendosa, Torrei, Sos Canales, Punta Gennarta) and hyper-eutrophic (Bidighinzu, Cixerri, Pranu Antoni) (Sechi & Lugliè 1992;Marchetto et al 2009) Crustacean zooplankton taxa composition Overall, we identified 21 crustacean zooplankton taxa, thirteen belonging to the Cladocera and eight to the Copepoda ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reservoirs were classified as eutrophic (Cantonieria, Mulargia, Gusana, Monte Lerno, Benzone, Is Barrocus, Leni and Cucchinadorza), mesotrophic (Medio Fludendosa, Torrei, Sos Canales, Punta Gennarta) and hyper-eutrophic (Bidighinzu, Cixerri, Pranu Antoni) (Sechi & Lugliè 1992;Marchetto et al 2009) Crustacean zooplankton taxa composition Overall, we identified 21 crustacean zooplankton taxa, thirteen belonging to the Cladocera and eight to the Copepoda ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Conductivity, DO, TN and RP were analyzed following Strickland & Parsons (1972) (Table 1). Data on the morphology, renewal time and trophy of all reservoirs were taken from previous studies (Sechi & Lugliè 1992Marchetto et al 2009). Qualitative samples were collected via vertical hauls with an Apstein zooplankton net (mesh size 200 µm), from 20 m depth to the surface, and preserved in 90% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Three phytoplankton composition metrics were proposed: the contribution of cyanobacteria (%) to total phytoplankton biovolume; the IGA (Índex de grups algals), also known as the Catalan Index (Catalan et al 2003); and the Mediterranean Phytoplankton Trophic Index (MedPTI; Marchetto et al 2009). These metrics have only been intercalibrated for deep and large reservoirs, but some could also be reliable in shallower reservoirs (Marchetto et al 2009) and thus could be suitable metrics for assessing the ecological status of the Pareja limno-reservoir under the WFD requirements.…”
mentioning
confidence: 99%
“…Therefore a good water management plan is essential. Most of the Sardinian reservoirs were eutrophic (Total Nitrogen, 594-2057 μg L -1 ; Total Phosphorus, 23-180 μg L -1 ), with phytoplankton communities dominated by CB (Sechi and Lugliè, 1996;Begliutti et al, 2007;Marchetto et al, 2009 Cabras et al (2013) (Supplementary Tab. 2), which refer to the period of the monitoring activities described in this paper.…”
Section: Discussionmentioning
confidence: 99%